Political Leadership in Parliament: The Role of Select Committee Chairs in the UK House of Commons - Kelso, Alexandra (2016)
Concepts of political leadership have been applied sparingly to parliaments, and not at all to the study of House of Commons select committees in the UK Parliament, where analysis has largely focused on their institutional capacity to scrutinise government and hold it to account. Yet examining these committees through a political leadership lens illuminates the complex role of committee chairs, a role which was significantly reshaped in 2010 with a shift to election of chairs by the whole House. This article analyses select committee chairs through the lens of political leadership, and draws on a series of interviews with chairs in order to delineate the nature of the political leadership they perform. It argues that, as chairs are now increasingly important parliamentary and policy actors, our understanding of them is significantly advanced by conceptualising their role as one of parliamentary political leadership, and that this in turn enriches our analytical toolkit when it comes to the study of parliaments.